Thermometric Bridge Circuits for Measuring Thermophysical Properties - Ihor Vasylkivskyi; Vasyl Fedynets; Yaroslav Yusyk (Energy Engineering and Control Systems, 2020)
The article presents the designs of a number of devices for measuring the thermal conductivity of solids developed using the new methodological approaches proposed by the authors, which enable measurements in a wide range of thermal conductivity values with better accuracy. The proposed approaches rely on the principle of invariance, which consists in ensuring the compensation of the effect of various non-informative parameters on the measurement result. For calculating the developed thermometric bridge circuits (balanced, unbalanced and partially balanced), there was applied the theory of thermal circuits based on the similarity between heat transfer and electricity transfer. The design of thermometric devices based on thermometric bridge circuits makes it possible to raise significantly the accuracy of measuring thermophysical properties of materials due to the reduced errors stemming from the effect of non-informative parameters on the measurement result. This, in turn, allowed the extended measurement range for the thermal conductivity, increased reliability and reduced cost of the devices owing to the simplified measuring circuit.